Rhetorical Resonance: Exploring the Role of Repetition and Parallelism in Pablo Neruda’s Poetic Style - Olasode, Chikodi Adeola (International Journal of Language and Literary Studies, 2025)
Pablo Neruda’s love poetry derives much of its poetic force from the deliberate use of repetition and parallelism, both of which constitute the poems’ emotional resonance and meaning. This essay examines the aesthetic, rhetorical, and affective valences of repetition and parallelism in the love poetry of Pablo Neruda, with particular attention to The Captain’s Verses. In this collection, Neruda’s iterative phrasing, syntax, and imageries act as the means through which desire, longing, and absence are intensified. These recurring patterns generate a rhythmic and musical cadence of repetition that is distinct. Guided by Roman Jakobson’s concept of poetic function, generative approaches of classical rhetoric, and stylistics based in contemporary scholarship, repetition and parallelism are analyzed as processes that assist interpretation and solicit interactivity as a reader. The strategies Neruda deploys mediate the porous boundary between private desire and communal emotion. This essay contends, through the close reading of Neruda’s emblematic poems and the integration of critical theory, that these poetic devices operate in synergistic concert as instruments of structural innovation, emotional amplification, and stylistic distinction.